Особливості обліку реалізації товарів із наданням знижок - Князь, С. В.; Залуцький, В. П.; Яворська, Н. П.; Kniaz, S. V.; Zalutskyi, V. P.; Yavorska, N. P. (Видавництво Львівської політехніки, 2017)
У статті досліджено сутність поняття «знижка». Виділено мету та завдання надання знижок у процесі реалізації товарів, охарактеризовано їхні найпоширеніші різновиди. Дослідження дало змогу виокремити характерні особливості відображення у вітчизняній системі обліку торговельних підприємств надання знижок під час реалізації товарів.

The process of selling goods (products and services), based on which determined that it plays a significant role in the commercial enterprises as directly affect the financial results of the enterprise – profit. This primarily concerns trade margins and discounts. In this scientific paper, by analyzing the research of domestic and foreign authors, defined the essence of discount. Allocated the goal and objectives of providing discounts in the process of sale of goods described their the most common differently species. The research made it possible to distinguish the characteristic features of reflection of providing discounts during the realization of goods in the national accounting system of commercial enterprises. Proved that correctly reflect the accounting process of sale of products (goods and services) with discounts accountants requires adequate knowledge about their features. Analyzed the order of accrued discounts in the sale of goods accounting company-seller and found that the accounting method depends on when and what discounts are applied. It is established that the use of trade discounts on the sale of goods is a way to attract more customers, increase sales and consequently increase income trading businesses. Argued that no reasonable amount of discounts could lead to discounts, which not only increase revenue, but also the cause of loss. It is advisable to note that the characteristics of the display of goods with discounts depending on when and applicable discounts – before or after the sale of goods; at prices higher or lower than their purchase price. Therefore, before modern accountants commercial enterprises face some problems when displaying the trade discount granted to the sale of goods who need to know the specifics of their account. A clear and proper display and writing accounting process, trade margins and selling goods with discounts and registration of all necessary documents will improve relationships with customers, increase the productivity of accounting personnel, their efficiency and reliability of accounting data and settlements with customers.
Features accounting implementation goods with the granting of discounts
Keywords: знижка; реалізація товарів; торговельне підприємство; облік; рахунок; discount; realization of goods; commercial enterprises; accounting; account; 657.444